1991
DOI: 10.1007/bf00251127
|View full text |Cite
|
Sign up to set email alerts
|

Tachykinin antagonists inhibit the morphine withdrawal response in guinea-pigs

Abstract: This study was an investigation of the effects of the tachykinin antagonists, spantide and (D-Pro4, D-Trp7,9,10)substance P 4-11, injected intracerebroventricularly (ICV), on the locomotor and behavioural responses of guinea-pigs to substance P (SP) injected ICV and to naloxone-induced morphine withdrawal. SP, 50 nmol, produced increased locomotor activity and behaviour that mimicked the response induced by injection of naloxone hydrochloride, 15 mg/kg, in guinea-pigs treated 2 h previously with morphine sulph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The reasons for these dierential eects are not known, but could be related to dierential action of CGRP 8-37 on the CGRP and substance P containing neurones in the dorsal horn. Currently, the role of substance P in opioid tolerance is largely unde®ned although previous studies have implicated this peptide in the development of physical dependence (Johnston & Chahl, 1991;Kreeger & Larson, 1993). An increase in the release of substance P could lead to the release of retrograde messengers and the attenuation of opioid receptor activity.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for these dierential eects are not known, but could be related to dierential action of CGRP 8-37 on the CGRP and substance P containing neurones in the dorsal horn. Currently, the role of substance P in opioid tolerance is largely unde®ned although previous studies have implicated this peptide in the development of physical dependence (Johnston & Chahl, 1991;Kreeger & Larson, 1993). An increase in the release of substance P could lead to the release of retrograde messengers and the attenuation of opioid receptor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Central injection of SP and selective NK 1 , NK 2 and NK 3 receptor agonists induced increased locomotor activity and other behaviors such as face-washing, grooming and wet-dog shakes [129][130][131][132][133]. The vocalization response induced in guinea-pigs by NK 1 receptor agonists was of particular interest since it was considered to be a stress-induced response [134].…”
Section: Tachykinins In Affective Disordersmentioning
confidence: 98%
“…Peptide SP antagonists [129] and a non-peptide NK 1 receptor antagonist [205] were reported to reduce the signs of opioid withdrawal in animals. The presence of tachykinins in the mesolimbic system suggested that they may also be involved in reward and reinforcing mechanisms which lead to addiction.…”
Section: Tachykinins In Drug Abusementioning
confidence: 99%
“…washing and lachrymation have been reported (Brent et al, 1988;Elliott et al, 1991;Johnston & Chahl, 1991;Chahl & Johnston, 1993). A controversy exists concerning the existence of NK2 tachykinin receptors in the central nervous system (Quirion & Dam, 1988;Saffroy et al, 1988;Dam et al, 1990;Hagan et al, 1993;Maggi et al, 1993a).…”
Section: Introductionmentioning
confidence: 98%